Synthesis and characterization of a 5-membered ring cyclic hydroxylamine coupled to triphenylphosphonium to detect mitochondrial superoxide by EPR spectrometry. (2nd December 2019) - Scheinok, Samantha; Driesschaert, Benoit; d'Hose, Donatienne; Sonveaux, Pierre; Robiette, Raphaël; Gallez, Bernard
Abstract: As mitochondrial superoxide is becoming an attractive metabolic and pharmacological target, there is an important need for developing analytical tools able to detect superoxide with high sensitivity and specificity. Among EPR-based methods, it has been recently reported that cyclic hydroxylamines offer a high sensitivity to measure superoxide production. Here, we report the synthesis and evaluation of mitoCPH, in which a 5-membered ring hydroxylamine was coupled to a triphenylphosphonium moiety to allow mitochondrial accumulation. MitoCPH efficiently reacted with superoxide with a bimolecular rate constant of 1.5 × 10 4 M −1 s −1 . We assessed the ability of this compound to detect superoxide in PBS buffer, lysates, and in paraquat-stimulated cells. We compared its performance with CMH, a nontargeted 5-membered ring hydroxylamine, and mitoTEMPO-H, a classically used 6-membered ring hydroxylamine targeted to mitochondria. MitoCPH presented a higher sensitivity for superoxide anion detection than commonly used mitoTEMPO-H, both in buffer and in cell lysates. While we have described the ability of mitoCPH to detect superoxide in different cellular media, we cannot exclude other potential contributors to the nitroxide production from this probe. Therefore, mitoCPH should be considered as a mitochondria-targeted probe and its use as selective superoxide probe should be used cautiously.